From Autonomy to Integration, From Integration to Dynamically Balanced Integrated Co-existence: Non-aging as the Third Stage of Development - Salnikov, Lev; Baramiya, Mamuka G. (Frontiers in Aging, 2021)
Reversible senescence at the cellular level emerged together with tissue specialization in Metazoans. However, this reversibility (ability to permanently rejuvenate) through recapitulation of early stages of development, was originally a part of ontogenesis, since the pressure of integrativeness was not dominant. The complication of specialization in phylogenesis narrowed this “freedom of maneuver”, gradually “truncating” remorphogenesis to local epimorphosis and further up to the complete disappearance of remorphogenesis from the ontogenesis repertoire. This evolutionary trend transformed cellular senescence into organismal aging and any recapitulation of autonomy into carcinogenesis. The crown of specialization, Homo sapiens, completed this post-unicellular stage of development, while in the genome all the potential for the next stage of development, which can be called the stage of balanced coexistence of autonomous and integrative dominants within a single whole. Here, completing the substantiation of the new section of developmental biology, we propose to call it Developmental Biogerontology.